Modern middens: Shell recycling for restoring an endangered marine ecosystem in Victoria, Australia. (31st August 2020) - Branigan, Simon; Fitzsimons, James; Gillies, Chris L.
Summary: Shellfish reefs are one of the most depleted marine ecosystems in the world, and there is considerable interest and efforts to restore the ecosystems. When degraded reefs require the addition of new substrate to support oyster re‐establishment, recycled shells can be used to rebuild new reef bases. Shell recycling as a means of procuring shells was first introduced in Australia by The Nature Conservancy in 2015, through the establishment of the 'Shuck Don't Chuck' Shell Recycling Project in Victoria. The recycling project was first piloted in the regional city of Geelong with the aim of providing sufficient quantity of clean, recycled shell to support reef base construction for shellfish reef restoration in Port Phillip Bay. The project has subsequently expanded into markets and restaurants in Melbourne. Community involvement and restoration promotion are important secondary outcomes of the programme. We provide lessons from our experience to date and a step‐by‐step guide of how to establish a shell recycling project from initial pilot and trial stages to a full programme. These steps include the following: (i) recruitment of shell recycling partners, (ii) transport and logistics, (iii) shell storage sites, (iv) biosecurity and curing protocols, (v) hatchery use, (vi) reef deployment, and (vii) community engagement. Shell recycling is an effective way to not only source substrate for restoring shellfish reefs, but also to reduce the amount of waste going to landfill and should be considered as part of any shellfish reef restoration project which utilises shell products.